2015
DOI: 10.1039/c5sc01538c
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of quinones for high power density biofuel cells

Abstract: Rationally designing quinones to label GDH and create a redox hydrogel that delivers high OCP, current and power densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 183 publications
(173 citation statements)
references
References 51 publications
8
163
1
1
Order By: Relevance
“…Once a series of electron mediators with suitable electronic properties has been selected, they must next be screened for their ability to interact with the enzyme in a similar fashion to a substrate; this has greater importance in cases where the redox cofactor is deeply buried within the protein structure. We recently demonstrated that naphthoquinone derivatives were able to undergo efficient MET with one type of glucose oxidizing enzyme, while another species did not exhibit any activity even though the enzymes possess the same redox cofactor where their potentials are expected to have negligible effect on the required overpotential of MET, reemphasizing the importance of cofactor accessibility by the electron mediator [27].…”
Section: Electron Transfer Mechanisms 21 Mediated Electron Transfermentioning
confidence: 99%
“…Once a series of electron mediators with suitable electronic properties has been selected, they must next be screened for their ability to interact with the enzyme in a similar fashion to a substrate; this has greater importance in cases where the redox cofactor is deeply buried within the protein structure. We recently demonstrated that naphthoquinone derivatives were able to undergo efficient MET with one type of glucose oxidizing enzyme, while another species did not exhibit any activity even though the enzymes possess the same redox cofactor where their potentials are expected to have negligible effect on the required overpotential of MET, reemphasizing the importance of cofactor accessibility by the electron mediator [27].…”
Section: Electron Transfer Mechanisms 21 Mediated Electron Transfermentioning
confidence: 99%
“…6 In EFCs, the fuels undergo bioelectrocatalytic oxidation at the anode operating commonly with flavin adenine dinucleotide-dependent (FAD) oxidases and dehydrogenases as well as nicotinamide adenine dinucleotidedependent (NAD) dehydrogenases. 5,[9][10][11] Metalloenzymes, such as laccases, bilirubin oxidase and peroxidase, are generally used at the cathode of EFCs allowing the bioelectrocatalytic reduction of O 2 or peroxides to H 2 O. [12][13][14][15] In addition to carbohydrates, other types of enzyme substrates have been reported as fuels such as alkanes, carboxylic acids, and other organic molecules.…”
mentioning
confidence: 99%
“…Furthermore, the EET efficiency of this strain could be improved by utilization of the currently known conductive pili (Holmes et al ., 2016) by, for instance, coproduction of conductive and adhesive pili in the same cell or by replacing the Fim pili with novel rationally designed hybrid pili that consist of a long conductive fibre and a terminal carbohydrate‐binding adhesin. Alternatively, the EET of E. coli cymA ‐ mtr ‐ fim could be promoted through penetration of the pili layer with electrode‐tethered conductive polymers such as linear naphtoquinone‐modified polyethylenimine hydrogels through which electrons can be transferred by shuttling between the covalently bound redox centres (Milton et al ., 2015). …”
Section: Resultsmentioning
confidence: 99%